Differences in Perception of the Participants in the Management Process and Its Real Trajectory - Olaf Flak; Adrian Pyszka (Journal of Entrepreneurship, Management and Innovation)

(untitled)
The aim of the paper is to present results of the research that was focused on managers’ behaviours. We tried to discover the main differences between the real trajectory and perception of managers in the field of two types of management processes. In the first part of the paper there is a theoretical foundation of process management and conclusions that led to a research model. In the second part we present the state of art in the field of human perception theories. Then, we describe assumptions of the research and methods of gathering data. What is important in the case of research method, an observation and a survey were used. The observation was done using the online management tools. During the research, managers were given a small project to lead. We recorded their actions and when their projects were completed, we asked them how they had acted. As a result of the research, there are three examples of description of managers’ behaviours and their perception. In the introduction we formulated two hypotheses and on the grounds of the research result we prove both statements in conclusion of the paper.